China Impact on Trade Integration of ASEAN - Díaz González, José Andrés (2017)
This article analyzes the process of trade integration of the member countries of Association of Southeast Asian Nations (ASEAN). Although the political integration of these countries is well established, a review of different economic andtrade indicators show a weak trade integration. By observing the effect of China’s trade policy in Asia, it is found that this helps strengthen trade integration of ASEAN; however, does not sufficiently for there to be a complete integration inthis regard.